The relationship of spatial visualization ability and number representation: evidence from multiple tasks - Mengxia Li; Yuning Chen; Jiahui Yang; Qiangqiang Wang; Xiaolin Ye (BMC Psychology)
Abstract It is well established in the literature that the relation of spatial ability and the number representation, but the intrinsic relation of spatial visualization ability and number representation are not well understood. In the Current study, Chinese Preschool children (N = 200; 107 girls; Mage = 5.47years, SD = 0.67) completed two kinds of spatial visualization tasks and six kinds of number representation tasks. The results showed that spatial visualization ability was positively correlated with number representation for 5 years-old Children. Furthermore, spatial visualization ability can positively predicted number representation. These findings are consistent with the view that spatial visualization is recognized for its potential to enhance numerical skills, encompassing competencies associated with fundamental number. Therefore, developing children’s spatial visualization ability may be an effective way to enhance their number representation skills. This has important implications for early education and intervention strategies.